JUAL BELI DENGAN SISTEM TRANSFER DANA MELALUI BANK DALAM PANDANGAN ISLAM - Syamsul Effendi (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
This article discusses the sale and purchase with payment through transfer system to banks in the city, outside the city/region or abroad. The discussion focused on revealing on how the transactionused transfers system, conditions and legal review of syar'i. The literature review is an approachused in this study through collecting various informations from related sources such as printmedia, electronic and internet. Transfering fund is performed from a customer's account to anothercustomer's account in a short time and secure manner. In this context, the transfer is a bank servicefor the transfer of funds from one branch to another as requested by the customer to be paid to therecipient in another branch of bank. This money transfer can be done for business purposes eitherin the city, outside the city or abroad. The Muslim scholars‟ views about bank transfer law are notfound directly even in the form of a fatwa on this matter. Hence, to find out how the law of buyingand selling with funds transfer through the bank must investigate their opinions on the system ofsale and purchase in general context and then compared it to the trading in the “Salam” system.Sale and purchase in Islamic Sharia is considered valid if it meets the conditions that have beendetermined such as ijab-qabul (from sellers and buyers) who are not separated by other words orsilent long enough. This requirement applies if both parties are in the aqad assembly, nevertheless,if one of the two parties is not in the aqad assembly the conversation and silence from the otherparty does not damage the qabul as long as he/she does not yet know the aqad news. In this sense,the aqad is assumed being prformed when a letter or representative from the other party comes tohim/her. In the sale and purchase transactions conducted by bank transfer, aqad (ijab-qabul) isfound from Muslim scholars‟ opinion, it is when the buyer receives offer both free offer and firmoffer, then the buyer examines and proposes changes as necessary to acceptance, then makingsales contract agreement. Thus, buying and selling through transfers is allowed in Islam inaccordance with the opinions of the scholars and the sale is comparable with the sale and purchaseof Salam.